Exercise Improves Testicular Morphology and Oxidative Stress Parameters in Rats With Testicular Damage Induced by a High-Fat Diet - Elmas, Merve Acikel; Ozakpinar, Ozlem Bingol; Kolgazi, Meltem; Sener, Goksel; Arbak, Serap; Ercan, Feriha (Wiley, 2022)
Obesity and male infertility are problems that affect population. Exercise is a nonpharmacological way to reduce the negative health effects of obesity. The purpose of this study was to examine the effects of exercise on hormone levels, blood-testis barrier, and inflammatory and oxidative biomarkers in rats that became obese due to a high-fat diet (HFD). Male rats received a standard diet (STD group) or a HFD (HFD group) for 18 weeks. During the final 6 weeks of the experiment, swimming exercises (1 h/5 days/week) were given to half of these animals (STD + EXC and HFD + EXC groups). Finally, blood and testicular tissues were analysed by biochemical and histological methods. Body weight, leptin, malondialdehyde, interleukin-6, TNF-alpha and myeloperoxidase levels, apoptotic cells and DNA fragmentation were increased, and testis weight, insulin, FSH, LH, testosterone, glutathione and superoxide dysmutase levels, proliferative cells, ZO-1, occludin, and gap junction protein Cx43 immunoreactivity were decreased in the HFD group. All these hormonal, morphological, oxidative and inflammatory biomarkers were enhanced in the HFD + EXC group. It is thought that exercise protected testicular cytotoxicity by regulating hormonal and oxidant/antioxidant balances and testicular function, inhibiting inflammation and apoptosis, as well as preserving blood-testis barrier.
Kolgazi, Meltem/0000-0003-4820-1904; Ercan, Feriha/0000-0003-2339-5669; Sener, Goksel/0000-0001-7444-6193
Keywords: Blood Testis Barrier; Exercise; High-Fat Diet; Oxidative Stress; Ultrastructure